Auricular Cartilage Resection for Treatment-Refractory Idiopathic Chronic Chondritis: A Case Series. Issue 1 (20th January 2022) - Gordon, Steven A.; Nassiri, Ashley M.; Driscoll, Colin L.; Carlson, Matthew L.; Patel, Neil S.
Abstract : Objective: Describe a series of cases of idiopathic chronic auricular chondritis refractory to antibiotics and steroids treated successfully with surgery. Study Design: Case series. Setting: Two tertiary academic medical centers. Patients: We analyzed four patients diagnosed with chronic auricular deformity, pain, and drainage for a period of 1 to 5 years who had failed prolonged treatment consisting of antibiotics, corticosteroids, and incision and drainage. All four patients were smokers, three were diabetic, and two had a history of bariatric surgery. Interventions: Operative subcutaneous partial auriculectomy (removal of diseased cartilage and excess skin) was performed. Main Outcome Measures: Resolution of pain and drainage, need for additional procedures, and reduction in narcotics required for pain control were analyzed. Results: Two of the four patients were given an immediate postoperative course of doxycycline and ciprofloxacin. With a minimum of 6 weeks' follow-up, all four patients had complete resolution of pain and recurrent drainage postoperatively. One patient requiring daily narcotic medication for pain and benzodiazepine for sleep preoperatively no longer required prescription medication. All specimens revealed chronic dermal and cartilage inflammation. Three of four cases had polymicrobial infection. One case had only skin contaminant growth on culture following multiple oral and parental antibiotic regimens. Conclusions: Surgical excision of diseased cartilage as a result of idiopathic chronic chondritis is an effective treatment in those cases refractory to antibiotics and incision and drainage, and should be considered in the treatment algorithm for similar patients, potentially offering definitive cure.